IS TOURISM THE SALVATION OR CONDEMNATION OF RURAL HERITAGE INHIDALGO? PULQUE AND TOURISM IN HUASCA DE OCAMPOABSTRACT - Velázquez García, Mario Alberto (Benemérita Universidad Autónoma de Puebla, 2020)
The areas dedicated to the cultivation of the pulque Maguey and pulque production suffered asignificant fall in the last decades of the twentieth century in Hidalgo. However, in recent yearsthere has been a slight rebound in pulque production in some areas dedicated to the cultivation ofthe plant from which the precious nectar is obtained. This growth is related, among other factors,to the boom in the consumption of pulque in places where there has been an increase in touristactivity, specifically in certain rural areas. The present work seeks to explore from the publicpolicy approach, the impact that tourism has on the conservation of a central element for theheritage landscape of Hidalgo such as the Pulque Maguey. In the same way, elements of theproblem will be presented and the scope of generating an investigation that seeks to analyze theeffect that the development of public policies on tourism has on the conservation or not, of theheritage landscape of the maguey in specific areas of the State de Hidalgo and its influence onthe social construction of the rural.